Clinical Data Analysis for Treatment of Adult Inguinal Hernia by TAPP or TEP - Cao, Chunhui; Shi, Xiaoyu; Jin, Wei; Luan, Fengming (Frontiers in Surgery, 2022)
Background: TAPP and TEP are the main surgical methods for the treatment of adult inguinal hernia, but it is still necessary to consider which surgical method to choose in clinical practice. Our study was to compare the efficacy of laparoscopic transabdominal preperitoneal repair (TAPP) and laparoscopic total extraperitoneal repair (TEP) in the treatment of adult inguinal hernia, and to explore which surgical method is a better choice. Methods: A retrospective analysis was conducted on 686 adult patients with inguinal hernia admitted to our hospital from January 2016 to December 2020. According to different surgical methods, they were divided into TAPP group (N=361) and TEP group (N=325). The two groups of patients were statistically analyzed, and the operation time, postoperative pain, postoperative hospital stay, postoperative complications and recurrence were compared between the two groups. Results: There were no significant differences in postoperative hospital stay, complications and recurrence rates between the two groups (P>0.05). The duration of operation in TEP group was significantly shorter than that in TAPP group, and the difference was statistically significant (P<0.001); In terms of postoperative pain, TEP group was better than TAPP group, and the difference was statistically significant (P<0.001). Conclusions: TAPP and TEP are safe and effective surgical methods in the treatment of adult inguinal hernia. However, compared with TAPP,TEP treatment of adult inguinal hernia can significantly shorten the operative time, reduce the intraoperative trauma, lower postoperative pain, and do not increase the rate of complications and recurrence, which is worthy of application and promotion.